Svetovni trgovinski sistem in omejitve suverenosti - Tratnik, Matjaž (Pravnik, 2013)
The monograph of dr. Irena Peterlin World Trade Organisation and State Sovereignty deals with the relationship between the State sovereignty, being one of the most important fundaments of international relations on one side, and the obligations, originating in the membership of international organisations, on the other. After an extensive description of the historical development of the principle of sovereignty, the author introduces the WTO and its legal system. Special attention is paid to the relationship between the WTO law and the law of its Member States, and especially of course to the relationship between the WTO law and the law of Slovenia and the EU. An important part represents the description of the dispute settlement mechanism of the WTO. In order to identify the relevant obligations of the Member States, the author analyses several WTO agreements. The most important case law is included in this part, as well. The conclusion of the author is, that the legalised concept of the "Westfalian" sovereignty characterised by the monopoly over the exercise of power within the territory of a State remains the core of the concept of sovereignty up to the present day. However, the provisions of international treaties have precedence over unilateral acts of States, which means the negation of the absolute concept of sovereignty. This can especially be illustrated by the WTO, where the Member States have accepted limitations of their sovereignty in exchange for free trade. The compulsory and very effective dispute resolution system within the WTO is to be seen as an important limitation of sovereignty, as well. Nevertheless, in spite of numerous limitations and transfer of powers to international institutions, the concept of sovereignty even though it is constantly developing and changing, remains one of the most important attributes of statehood.
Keywords: globalizacija; globalization; gospodarsko pravo; mednarodna trgovina; mednarodno pravo; ocene in poročila; Peterlin, Irena: Svetovna trgovinska organizacija in državna suverenost; suverenost; Svetovna trgovinska organizacija